Inside Back Cover: Locked‐in Biomimetic Surface Gradients that are Tunable in Size, Density and Functionalization (ChemPhysChem 16/2014). Issue 16 (10th November 2014) - Krabbenborg, Sven O.; van Weerd, Jasper; Karperien, Marcel; Jonkheijm, Pascal; Huskens, Jurriaan
<x xml:space="preserve">Abstract</x> The image shows a microfluidic bilayer device (top), gradient formation (top right), locking and functionalization of the gradient (center left), and proteins that are assembled on this gradient (bottom), as reported by M. Karperien, P. Jonkheijm, and J. Huskens, on p. 3460.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>